Life Cycle Cost Analysis And Payback Period of 12-Kw Wind Turbine For a Remote Telecommunications Base Station In Malaysia - Azmi, A.; Sebayang*, Abdi Hanra; Harjon, Aditiya (Graduate School of Universitas Syiah Kuala, 2023)
Owing to the unavailability of electricity in many remote areas in Peninsular and East Malaysia, these areas do not have access to telephone signals. In remote areas, a diesel generator is used as the power source for the telecommunications base station. Hence, the continuous supply of diesel (which is a fossil fuel) is necessary in these remote areas. In this study, an attempt is made to assess the potential of replacing diesel-generated electricity with wind energy, which is renewable energy. Life cycle cost analysis is carried out, and the payback period of a wind energy system is determined for a remote telecommunications base station in Malaysia. The load characteristics and wind data are obtained from the Mersing Meteorological Station, Malaysia, and it was found that the annual load and base load are 12 kW. Hence, a 12-kW wind turbine is selected for the life cycle cost analysis at the site. The results show that the total specific cost of the 12-kW wind turbine is MYR 0.27/kWh based on a discount rate of 5% and electricity tariff in Malaysia of MYR 0.28/kWh. The payback period and discounted payback period of the 12-kW wind turbine are estimated to be 11.8 and 18.2 yr, respectively. Based on the load characteristics in Mersing, Malaysia, the 12-kW wind turbine is economically viable for the remote telecommunications base station. Nonetheless, the 12-kW wind turbine is not economically viable because the simple payback period is greater than 1/3 of the wind turbine's lifetime, which is 20 years. The 12-kW wind turbine, on the other hand, is suitable for use as a remote telecommunications base station.